Renal Intercalated Cells: Alien Cells Inside Us? - Miguel Luis Graciano (Biology)
Mammalian renal intercalated cells are known for their role in acid secretion and maintaining acid–base balance. Herein, we discuss the theoretical reasons behind their development based on published data, focusing on the unique characteristics of renal intercalated cell biology that distinguish them from other mammalian cell types, while simultaneously attempting to explain the persistence of cells similar to intercalated cells throughout evolution. In addition, we traced these characteristics phylogenetically back to the simplest organisms. Intercalated cells have several functions and attributes. First, they contribute to kidney defense mechanisms in response to both infectious and non-infectious kidney damage. Second, intercalated cells are energized by V-ATPases in a manner similar to that of protozoa. Third, they possess T-antigens, which are commonly found in embryonic and cancer cells and which confer invasive abilities to these cells. Fourth, their plasticity enables the regeneration of other epithelial cells. These observations indicate that the origins of renal intercalated cells may be traceable back to amoeboid cells that originated from an evolutionary lineage including protists, or even to the last eukaryote common ancestor. The theoretical framework presented herein supports two predictions: first, that sponge amoebocytes possess membrane V-ATPase and are sensitive to bafilomycin, but not to ouabain; and second, that sponge amoebocytes—along with cells from diploblasts (such as Xenacoelomorpha), cnidarians, worms, fish and mollusk ionocytes, and the entire cell lineage containing V-ATPase, carbonic anhydrase, and anion exchangers (HCO3−/Cl−)—have innate immunity, cellular dedifferentiation, and regeneration capabilities.